Santayana Read, finally, from an European Philosophical Context - Moreno Moreno, Daniel (Analysis. Journal of Philosophical Research, 2019)
Katarzyna Kremplewska, Life as Insinuation. George Santayana's Hermeneutics of Finite Life and Human Self. State University of New YorK Press, Nueva York, 2019, 288 pp., $85.00.